Monetary policy reaction function in turbulent period: The case of Nigeria - Elias A. Udeaja (West African Journal of Monetary and Economic Integration, 2020)
This paper utilizes a modified structural VAR (SVAR-X) model to analyse the process of monetary policy reaction function in turbulent period compared to the period of tranquillity. The study finds that it is crucial to distinguish between the response of monetary policy to output growth and inflation and across turbulent period compared to periods of tranquillity. Equally deciphered from the finding of the study is the fact that monetary policy and its effectiveness, particularly in the context of Nigeria cannot be examined without taking into consideration the peculiarity of her economy's reliance on oil and oil prices. This among others, is an indication that the effectiveness of monetary policy in Nigeria is episodic and ignoring such episodic feature may not only undermine any inference drawn from analysis of monetary policy but by extension capable of leading to wrong policy prescription.
Keywords: E44; E52; E58; 330; Monetary Policy Reaction Function; Asymmetric; Uncertainty; Developing Economies